Psychological barriers in children: an exploratory study on Dengue transmission using an adapted DIPB scale - Schimmelpfeng, Pedro; Lapa, Luiz Gonzaga; Lyra Pato, Claudia Marcia (Frontiers in Psychology, 2024)
Dengue is an arboviral infection found in tropical and subtropical regions transmitted by hematophagous mosquitoes from the genus Aedes spp. and responsible for millions of cases every year. Public campaigns and educational curriculum are designed to educate people, including children. However, what has been reported is that many decide not to follow these guidelines, even though they allegedly know what has to be done. To understand this phenomenon, this study aims to identify psychological barriers behind the adoption of pro-environmental behaviors that seek to reduce Aedes aegypti’s population. For that, middle school students participated on two studies responsible for (1) adapting the Dragons of Inaction Psychological Barrier (DIPB) scale to the target group (n = 150) and then (2) testing it on a larger group (n = 449). In the exploratory factor analysis, Bartlett correlation (p < 0.001), Cronbach’s alpha (0.83), and KMO analysis (overall MSA = 0.84) showed that data was suited for factor analysis. Five factors were retained by Kaiser Criterion and scree test (i.e., Conflicting goals and unnecessary changes—α 0.76, Interpersonal relations—α 0.72, Conflicting goals and lacking knowledge—α 0.58, Tokenism—α 0.73, and Tokenism toward the government—α 0.66). After that, the scale was tested across 11 different schools, where students also answered a questionnaire about the mosquito. Results suggested that the factors Conflicting goals and lacking knowledge and Tokenism toward the government presented a higher level of agreement for all students (means: 2.6 and 2.12 out of five, respectively). Those who scored higher in the mosquito’s questionnaire had factors Conflicting goals and unnecessary change and Interpersonal relations inhibited when compared to others (p < 0.05). These results suggests that future educational campaigns should build different actions that focuses on addressing both internal and external factors, creating a mosaic of projects, with different goals, each aiming different environmental challenges.